The Effect of inspiratory muscle training on respiratory muscle strength in patients undergoing high thoracic and abdominal surgery: An Integrative Review - Bruna Marques de Brito; Paula Christiane Canassia; Taisa Maria Fernandes; João Victor Martins Bernal da Silva; Danilo Cândido Bulgo; Fabrício Vieira Cavalcante; Luciana Moreira Motta Raiz; Hugo Celso Dutra de Souza; Tábata de Paula Facioli (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Respiratory muscle training can mitigate respiratory muscle dysfunction resulting from thoracic and upper abdominal surgeries. This integrative review aimed to describe the effects of inspiratory muscle training (IMT) on respiratory muscle strength in patients post-thoracic and upper abdominal surgery. The searches in the PubMed, Lilacs, and Scielo databases used scientific descriptors. Controlled and uncontrolled clinical trials published in the last ten years (from 2013 to 2023) in English or Portuguese, corresponding to the study objective, were included. Three independent researchers selected and analyzed the studies. Twenty-eight trials were found. Of these, seven were analyzed. Most studies involved individuals under 40 years of age, pre-obese, and individuals who underwent cardiac/thoracic surgery (myocardial revascularization, valve replacement, or both). Inspiratory muscle training was present in all included trials. Regarding duration, two studies conducted the intervention with IMT only in the immediate postoperative period and on the first postoperative day, one study conducted it for an indefinite period, according to the hospitalization period, three studies conducted IMT between seven and twelve weeks, and one study extended the training time for up to 12 months. Finally, IMT is indicated during hospitalization to promote inspiratory muscle strength gain in patients after high thoracic and abdominal surgeries. We also emphasize the need for standardization of protocols and therapeutic strategies in the respiratory rehabilitation of these patients. Therefore, respiratory physiotherapy needs to integrate IMT into the rehabilitation routine of these patients, aiming to prevent and treat respiratory complications and reduce hospitalization time and, morbidity and mortality.